ANALISIS YURIDIS TERHADAP KEBERADAAN LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER (LGBT) DI INDONESIA DALAM PERSPEKTIF HUKUM POSITIF - Reza Dipta Prayitna (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
Lesbian, Gay, Bisexual and Transgender (LGBT) phenomena are a minority group that is asking for recognition to be legalized and wants to change the social order in which its existence uses human rights as its legal protection. But when viewed from the noble ideals of the Indonesian people, the legalization of the existence of LGBT cannot be justified. Because the human rights in force in Indonesia are particular human rights adopted from the noble ideals of this nation. Until now, LGBT actors have often corrected and campaigned for their wishes so that same-sex marriage would be legalized. As a country based on the One Godhead, the campaign and speech made by LGBT actors are unacceptable even though human rights regulate freedom of speech and opinion. The Indonesian perspective as the Pancasila Law State towards the existence of LGBT still views Pancasila as the source of all legal sources, even though the rules governing LGBT behavior are not clearly available to ensnare the perpetrators. The hope of the people in the Indonesian Government is that LGBT behavior can be ensnared by imprisonment because it is not in accordance with the principles of life of this nation. Key words: Existence, LGBT, Indonesian law, Human rights